Cross-border trade in the European economic convergence system - Ukhnal, Nataliia; Purdenko, Olena; Melnik, Victoryia; Klymenko, Kateryna (European Spatial Research and Policy, 2025)
The article examines cross-border trade dynamics within the framework of European economic convergence, focusing on trade between Ukraine, Poland, Romania, Slovakia, and Hungary. It aims to shed light on trade trends, implications in the context of economic integration, and convergence efforts. The study provides a comprehensive analysis of trade channels, outlining the economic convergence goals and principles within the European context and highlighting the importance of trade. It explores specific trade channels between Ukraine and its neighbouring countries, analyses data, and assesses the impact on economic development and convergence efforts. The findings contribute to understanding the role of trade in promoting cohesion.